2021
DOI: 10.31234/osf.io/yra6v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief Report: Predictors of Adolescent Mental Health and Wellbeing During the COVID-19 Pandemic

Abstract: Purpose: This study explored predictors of COVID-19-related stress and wellbeing of Scottish adolescents during the COVID-19 lockdown to identify potentially malleable risk and protective factors.Methods: 5,548 participants were surveyed regarding stress, loneliness, wellbeing, schoolwork, support from school, and interaction with friends and family. Multiple linear regressions within a structural equation modelling framework were fit to predict COVID-19-related stress and wellbeing during the UK’s first lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Regarding lockdown experience, mean scores for this were significantly lower than those in phase 1, suggesting that adolescents had a harder and less enjoyable experience. This is consistent with several studies that have found the lockdown reduces wellbeing, and that the experience is worse the longer it lasts (Evans et al, 2021; Mead et al, 2020; Murat Baldwin et al, 2021). Furthermore, there is some evidence to suggest that adolescents experienced increased self‐harming behavior and a loss of hope and motivation for the future in the second UK lockdown, owing to the fact that the second lockdown was more difficult to cope with than the first (Wong et al, 2022; YoungMinds, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding lockdown experience, mean scores for this were significantly lower than those in phase 1, suggesting that adolescents had a harder and less enjoyable experience. This is consistent with several studies that have found the lockdown reduces wellbeing, and that the experience is worse the longer it lasts (Evans et al, 2021; Mead et al, 2020; Murat Baldwin et al, 2021). Furthermore, there is some evidence to suggest that adolescents experienced increased self‐harming behavior and a loss of hope and motivation for the future in the second UK lockdown, owing to the fact that the second lockdown was more difficult to cope with than the first (Wong et al, 2022; YoungMinds, 2021).…”
Section: Discussionsupporting
confidence: 91%